Co (at) SP S-1 catalyst and preparation method and application thereof

The Co@SP S-1 catalyst was prepared by dissolution-recrystallization method, which solved the noble metal dependence and stability of cobalt-based catalysts in the alkane dehydrogenation process, and achieved efficient and stable light alkane dehydrogenation reaction.

CN120286057APending Publication Date: 2025-07-11DALIAN UNIV OF TECH

Patent Information

Application Number
CN202510428711.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-07-11

AI Technical Summary

Technical Problem

The existing cobalt-based catalysts have problems such as precious metal dependence, insufficient environmental compatibility, carbon deactivation and high energy consumption in high temperature operation during the alkane dehydrogenation process. Traditional preparation methods lead to uneven metal distribution and insufficient stability.

Method used

The Co@SP S-1 catalyst was prepared by dissolution-recrystallization method. By treating the SP S-1 molecular sieve with organic alkali solution in an alkaline environment, a negative charge layer was formed to adsorb Co species, and a highly dispersed Co species was encapsulated in the molecular sieve framework through hydrothermal crystallization and calcination, forming a stable metal confined structure.

Benefits of technology

The directional positioning of Co species in the molecular sieve pores is achieved, the activity and stability of the catalyst is improved, energy consumption is reduced, and the preparation process is simplified, and the preparation process is good economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120286057A_ABST
    Figure CN120286057A_ABST
Patent Text Reader

Abstract

The invention discloses a Co (at) SP S-1 catalyst and a preparation method and application thereof, Co in the catalyst is highly dispersed in an SP S-1 molecular sieve, a part of Co is packaged in a self-pillared SP S-1 molecular sieve framework in a form of-Co-O-Si-, the proportion of Co species on the surface of the molecular sieve, in pore channels and at cross pore channel positions is greater than or equal to 70%, and the coating amount of Co in the catalyst is 1-12wt%. The preparation method comprises the following steps: by taking SPS-1 molecular sieve powder as a raw material, obtaining Co / SPS-1 by adopting an impregnation method, mixing the Co / SPS-1 with an organic alkali solution, and carrying out hydrothermal treatment to obtain the Co (at) SPS-1 catalyst. Compared with a conventional supported catalyst, the coated catalyst disclosed by the invention has highly dispersed adjustable metal sites, and metal species can be embedded into a molecular sieve framework; the catalyst has abundant accumulated mesopores among crystal grains, so that the active sites of the catalyst can be in rapid contact with reactant molecules; and the preparation method is simple, the used raw materials are cheap and easy to obtain, and certain economic benefits are achieved. The Co (at) SP S-1 catalyst is used for a light alkane dehydrogenation reaction and shows excellent catalytic performance and high reaction stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalytic chemistry, and relates to a Co@SP S-1 catalyst, a preparation method thereof and an application thereof. Background Art

[0002] Light olefins (propylene and ethylene), as key platform chemicals in the modern petrochemical industry, are not only the core raw materials for synthesizing polymers such as plastics and fibers, but also an indispensable cornerstone for the production of fine chemicals. Especially in the context of the ethylene-propylene industrial chain supporting more than 80% of global chemical products, the innovation of their production technology has always been the focus of attention in the academic and industrial circles. The process for preparing light olefins based on catalytic dehydrogenation (Dehydrogenation, DH) of light alkanes has been applied on a large scale.

[0003] In the alkane dehydrogenation technical route, CO2-assisted oxidative dehydrogenation (CO2-ODH) of light alkanes exhibits unique advantages. Compared with the traditional O2 oxidative dehydrogenation process, CO2, as a mild oxidant, has dual regulation characteristics: its weak oxidizing property can effectively inhibit the excessive cracking caused by the deep oxidation of alkanes, and at the same time, it can in-situ consume the by-product H2 through the reverse water-gas shift reaction (RWGS), significantly improving the thermodynamic equilibrium conversion rate. It is worth noting that while realizing the efficient preparation of light olefins, this process can convert CO2 into high-value syngas components such as CO, providing an innovative path for constructing a green industrial chain integrating "carbon cycle - energy conversion - chemical production".

[0004] The traditional metal oxides and supported metal catalysts in the current alkane dehydrogenation technical route still face three challenges: ① The high-temperature operation window (>600 °C) leads to excessive energy consumption; ② The carbon deposition deactivation phenomenon restricts the continuous operation cycle of the device; ③ The dependence on precious metals and the environmental incompatibility brought by by-product emissions. Therefore, the development of new catalysts with high activity, anti-carbon deposition characteristics and CO2 directional conversion ability has become the core breakthrough point for promoting the upgrading of light alkane dehydrogenation technology.

[0005] Due to the high catalytic activity, excellent selectivity, good stability, cost and environmental friendliness of cobalt-based catalysts, they are widely used in industrial reactions such as hydrocarbon cracking, syngas conversion and Fischer-Tropsch synthesis. At present, the preparation methods of cobalt-based catalysts are mainly divided into one-step synthesis method and post-treatment method, and different treatment methods have a huge impact on the activity and stability of the catalysts.

[0006] Patent CN118179584A discloses a preparation method of a Co-based propane dehydrogenation catalyst. After acid-treating molecular sieves in a concentrated nitric acid solution, they are ground in a mortar together with a Co precursor to obtain a supported Co-based catalyst. The catalyst prepared by this method has insufficient performance stability and is extremely dependent on the grinding method. Patent CN119608232A discloses a method for preparing a supported cobalt-based catalyst by an impregnation method. A Co salt is dissolved in a solvent to form an impregnating solution, which is mixed evenly with molecular sieves and then centrifuged, dried, and calcined to obtain cobalt-based molecular sieves. However, the cobalt oxide particles on the surface of the cobalt-containing molecular sieves prepared by the impregnation method are uneven in size, resulting in a lot of encapsulated cobalt being unable to participate in the reaction.

[0007] Yu et al. from Jilin University reported that Co-encapsulated S-1 molecular sieves were synthesized in one step by a ligand protection method. In the one-step method, the introduction of metal elements may interfere with the crystallization process of molecular sieves, resulting in uneven distribution of metal active sites, limited metal loading, high preparation cost, complex process, and the template agent used has high toxicity and insufficient environmental compatibility. (Journal of the American Chemical Society 2024, 146(13), 8939 - 8948) Summary of the Invention

[0008] Based on the problems of noble metal dependence and insufficient environmental compatibility faced by the above traditional alkane catalysts, the present invention provides a Co@SP S-1 catalyst, its preparation method and application. The short b-axis structure of the SP S-1 molecular sieve can significantly shorten the diffusion path of molecules in the pore channels. Combining with the steric hindrance effect, the Co species are directionally positioned at the intersecting pore channels of the molecular sieve. The post-treatment process further promotes the migration of Co species to the intersecting pore channels. The Si-OH on the surface of the molecular sieve is deprotonated in an alkaline environment (TBAOH) to form a negatively charged layer, which promotes TBA + to adsorb on the Si-O - sites through electrostatic interaction, inhibiting the dissolution on the outer surface. At the same time, the silicate oligomers dissolved inside the crystal react with TBA + to form intermediate states and sub-crystals. The continuous dissolution-recrystallization process drives the highly dispersed Co species to be encapsulated in the molecular sieve framework, finally forming a metal confinement structure with stable coordination. The Co@SP S-1 prepared by this method has an interdigitated self-pillared SP structure, rich mesoporous structure, simple preparation process, highly dispersed Co species, and can directionally regulate the position of Co species in the molecular sieve pore channels. At the same time, a part of Co is successfully encapsulated in the molecular sieve framework and has excellent catalytic performance in the dehydrogenation reaction of light alkanes.

[0009] The technical solution of the present invention is as follows:

[0010] A Co@SPS-1 catalyst, in which Co is highly dispersed in the SPS-1 molecular sieve. A part of Co is encapsulated in the self-pillared SPS-1 molecular sieve framework in the form of -Co-O-Si-. On the surface and inside the pores of the molecular sieve, the proportion of Co species at the cross-pore positions is ≥70%, and the coating amount of Co in the catalyst is 1-12 wt%.

[0011] The preparation method of the Co@SPS-1 catalyst includes the following steps:

[0012] (1) Dissolve the cobalt salt in deionized water, then add the SPS-1 molecular sieve thereto, and stir while heating in a water bath;

[0013] (2) After the water bath, dry the sample, mix it with the organic base solution, and transfer it to a hydrothermal autoclave for crystallization;

[0014] (3) After crystallization, filter, wash, dry, and calcine the obtained solid to obtain the Co@SPS-1 catalyst.

[0015] In step (1), the mass ratio of the cobalt salt solution to the SPS-1 molecular sieve is 5-15:1.

[0016] In step (1), the water bath temperature is 60-80°C, and the stirring time is 2-4 h.

[0017] In step (2), the organic base solution is selected from a n-butylamine solution or a tetrabutylammonium hydroxide solution.

[0018] In step (2), the concentration of the organic base solution is 0.05-0.55 mol / L.

[0019] In step (2), the mass ratio of the organic base solution to the SPS-1 molecular sieve is 2.5-15:1.

[0020] In step (2), the crystallization temperature is 120-180°C, and the crystallization time is 24-72 hours.

[0021] In step (3), the calcination temperature is 540-600°C, and the calcination time is 360-600 min

[0022] In step (1), the preparation method of the SPS-1 molecular sieve includes stirring and mixing the silicon source, the template agent, and water evenly, placing them in a hydrothermal autoclave for crystallization, and filtering, washing, drying, and calcining the obtained solid to obtain the self-pillared SPS-1 molecular sieve.

[0023] The silicon source is selected from one or more of silica sol, tetraethyl orthosilicate, and fumed silica.

[0024] The template agent is selected from a tetrapropylammonium hydroxide solution or a tetrabutylammonium hydroxide solution.

[0025] During the preparation of SP S-1 molecular sieve, the crystallization temperature is 120-160 °C, and the crystallization time is 24-72 hours; the calcination temperature is 540-600 °C, and the calcination time is 360-600 min.

[0026] The present invention also provides an application of the Co@SP S-1 catalyst in the dehydrogenation reaction of light alkanes.

[0027] The reaction temperature is 500-700 °C, and the reaction space velocity is 3000-12000 mL / g·h.

[0028] The light alkanes include ethane or propane.

[0029] Compared with the existing modification technologies, the beneficial effects that can be produced by this application are as follows: Through a simple and easy-to-operate dissolution-recrystallization method, using relatively inexpensive and easily available template agents and silicon sources, a coated catalyst with highly dispersed and adjustable metal sites and metal species that can be embedded in the molecular sieve framework is successfully prepared. The catalyst also has abundant intergranular packing mesopores, which is beneficial for the rapid contact between the active sites of the catalyst and the reactant molecules; it has good diffusion performance, and is easy to repeat and scale up production during the synthesis process, with good economic and environmental benefits. The above advantages make the catalyst perform excellently in the dehydrogenation reaction of light alkanes and have high application value. Description of the Drawings

[0030] Figure 1 XRD spectra of the samples prepared from sample 1#, 2# of the present invention, comparative sample D1#, D2#, and example sample P11#.

[0031] Figure 2 Hydroxyl infrared spectra of the samples prepared from sample 1#, 2# of the present invention, comparative sample D1#, D2#, and example sample P11#.

[0032] Figure 3 UV spectra of the samples prepared from comparative sample D1#, D2# and example sample P11# of the present invention. Detailed Description of the Invention

[0033] The following describes this application in detail with reference to the examples, but this application is not limited to these examples.

[0034] Unless otherwise specified, the raw materials in the examples of this application are all purchased through commercial channels.

[0035] Unless otherwise specified, the analysis methods in the examples adopt the conventional settings and conventional analysis methods of the instruments.

[0036] The analysis methods in the examples of this application are as follows:

[0037] X-ray diffraction (XRD) analysis of the sample: The analysis instrument was a DX-2700B X-ray diffractometer produced by Dandong Haoyuan Instrument Co., Ltd. The analysis conditions were CuKα radiation source, tube voltage of 45 kV, tube current of 200 mA, scanning step of 0.02°, and scanning range of 2θ = 5 - 40°.

[0038] Physical adsorption characterization of nitrogen on the sample: The analysis instrument was a JW-BK200C specific surface area and pore size analyzer produced by Beijing Jingwei Gaobo Science and Technology Co., Ltd. The analysis conditions were as follows: 0.15 g of the powdered catalyst was pressed into a tablet and then loaded into a quartz adsorption tube, which was treated under vacuum conditions at 350 °C for 6.5 h to remove moisture and impurities in the sample. Nitrogen adsorption and desorption experiments were carried out at a temperature of 77.4 K. The Brunauer-Emmett (BET) equation was used to calculate the internal specific surface area of the sample, and the t-plot method was used to calculate the internal specific surface area, external surface area, and pore volume of the molecular sieve sample. The total pore volume was calculated based on the nitrogen adsorption amount at a relative pressure P / P0 = 0.99.

[0039] Infrared characterization of the sample: The spectrum of surface hydroxyl (OH) vibration was recorded using a Nicolet IS50 infrared spectrometer, and the test range was 4000 - 400 cm -1 , the number of scans was 15 times, and the optical resolution was 4 cm -1 . The test method was as follows: 20 mg of the powdered sample was weighed, pressed into a thin slice using a tablet press, and loaded into an infrared test cell. It was pre-treated by heating to 400 °C at a heating rate of 10 °C / min; after the pre-treatment was completed, it was cooled to room temperature and then tested.

[0040] Ultraviolet-visible spectrophotometry (UV-vis) test of the sample: The sample was tested using a UV-550 ultraviolet spectrophotometer produced by Agilent Technologies, Inc. of the United States to analyze the existence form of metal species on the molecular sample. The test conditions were: using BaSO4 as a reference, and the scanning range was 190 nm - 800 nm.

[0041] Sample Example 1

[0042] 15 g of tetraethyl orthosilicate, 14 g of tetrabutylammonium hydroxide, and 4.55 g of water were weighed and mixed and stirred evenly, then placed in a hydrothermal autoclave at 130 °C for crystallization for 72 h. The obtained sample was centrifuged and then placed in an oven at 110 °C overnight for drying, and then calcined at 540 °C for 6 hours to obtain SPS-1 molecular sieve powder, denoted as Sample 1#.

[0043] Sample Example 2

[0044] Weigh 0.75 g of NaOH and 48.6 g of sodium silicate, add them to 22.5 g of deionized water, add 2.50 g of methyltriethoxysilane and stir evenly, then add 30.7 g of tetrapropylammonium hydroxide (TPAOH), and stir at room temperature for 6 hours to obtain a sol; place the obtained sol in a hydrothermal autoclave at 170 °C for crystallization for 25 hours; the obtained solid is filtered, dried at 110 °C for 8 hours, and calcined at 540 °C for 10 hours to obtain Silicalite-1 molecular sieve powder, denoted as sample 2#.

[0045] Comparative Example 1

[0046] Dissolve 6.74 g of Co(NO3)2·6H2O in 40 mL of deionized water. After complete dissolution, add 10 g of SPS-1 molecular sieve (sample 1#) to the solution. After water bath at 80 °C and 300 rpm / min for two hours, centrifuge the sample and place it in an oven at 110 °C overnight to dry. Then, calcine the obtained solid in air at 540 °C for 3 hours.

[0047] The sample is denoted as D1#

[0048] Comparative Example 2

[0049] Dissolve 6.32 g of Co(NO3)2·6H2O in 40 mL of deionized water. After complete dissolution, add 10 g of Silicalite-1 molecular sieve (sample 2#) to the solution. After water bath at 80 °C and 300 rpm / min for two hours, centrifuge the sample and place it in an oven at 110 °C overnight to dry. Then, calcine the obtained solid in air at 540 °C for 3 hours. The sample is denoted as D2#

[0050] Example 1

[0051] Dissolve 6.74 g of Co(NO3)2·6H2O in 40 mL of deionized water. After complete dissolution, add 10 g of SPS-1 molecular sieve (sample 1#) to the solution. After water bath at 80 °C and 300 rpm / min for two hours, place the sample in an oven at 110 °C overnight to dry. Weigh 1.5 g of the obtained sample, add 0.47 g of tetrabutylammonium hydroxide and 7.03 g of deionized water, pour it into a hydrothermal autoclave, and hydrothermally crystallize at 130 °C for 24 h. Centrifuge the sample to neutrality and dry it, and calcine it in air at 600 °C for 6 hours. The sample is denoted as P1#

[0052] Examples 2-4 are different from Example 1 in the concentration of alkali treatment

[0053] The operation is the same as that in Example 1, except that only the concentration of alkali treatment is changed (Table 1), and other operations are the same.

[0054] Table 1 Examples under different alkali treatment concentrations

[0055] Example Number Sample Number Amount of Organic Base Added Example 2 P2 0.93g Example 3 P3 1.35g Example 4 P4 1.76g

[0056] Example 5

[0057] Dissolve 6.74 g of Co(NO3)2·6H2O in 40 mL of deionized water. After complete dissolution, add 10 g of SP S-1 molecular sieve (Sample 1#) to the solution. After two hours of water bath at 80 °C and 300 rpm / min, place the sample in an oven at 110 °C and dry it overnight. Weigh 1.5 g of the obtained sample, add 0.93 g of tetrabutylammonium hydroxide and 6.57 of deionized water, pour it into a hydrothermal autoclave, and hydrothermally crystallize it at 120 °C for 24 h. Centrifuge the sample to neutrality and dry it, and calcine it in air at 600 °C for 6 hours. The sample is denoted as P5#

[0058] Examples 6 - 9

[0059] The operation is the same as that in Example 5, except that only the recrystallization temperature is changed (Table 2), and other operations are the same.

[0060] Table 2 Examples at different crystallization temperatures

[0061] Example Number Sample Number Temperature Example 6 P6 140℃ Example 7 P7 150℃ Example 8 P8 160℃ Example 9 P9 170℃

[0062] Example 10

[0063] Dissolve 6.74 g of Co(NO3)2·6H2O in 40 mL of deionized water. After complete dissolution, add 10 g of SP S-1 molecular sieve (Sample 1#) to the solution. After two hours of water bath at 80 °C and 300 rpm / min, place the sample in an oven at 110 °C and dry it overnight. Weigh 1.5 g of the obtained sample, add 0.93 g of tetrabutylammonium hydroxide and 6.57 of deionized water, pour it into a hydrothermal autoclave, and hydrothermally crystallize it at 160 °C for 36 h. Centrifuge the sample to neutrality and dry it, and calcine it in air at 600 °C for 6 hours. The sample is denoted as P10#

[0064] Examples 11 - 13

[0065] The operation is the same as that in Example 10, except that only the crystallization time is changed (Table 3), and other operations are the same.

[0066] Table 3 Examples at different crystallization times

[0067] Example Number Sample Number Crystallization Time Example 11 P11 48h Example 12 P12 60h Example 13 P13 72h

[0068] Perform XRD characterization and calculate the relative crystallinity, and physical adsorption characterization on the above samples. Taking Sample 1#, 2#, comparative samples D1#, D2#, and example samples P2#, P8#, P11# as examples, the data are shown in Table 4 and Figure 1 as follows. From Figure 1It can be seen that at the same Co loading, the characteristic diffraction peak of Co3O4 appeared in Comparative Example D2#, indicating the aggregation of Co species on the D2# sample. However, no characteristic diffraction peak of Co3O4 was observed in Example samples P2#, P8#, and P11#, indicating that Co species were highly dispersed on the SP S-1 support. Compared with samples 1# and 2#, the relative crystallinity of Comparative Example samples D1# and D2# loaded with metallic Co decreased significantly, and the total specific surface area and micropore specific surface area of the materials decreased substantially. After "dissolution-recrystallization", Example P2#, P8#, and P11# showed significant improvement and recovery in pore distribution.

[0069] Table 4 Relative crystallinity and physical adsorption test characterizations of various samples

[0070]

[0071] The above samples were characterized by hydroxyl infrared spectroscopy. Taking samples 1# and 2#, Comparative Example samples D1# and D2#, and Example sample P11# as examples, the results are as Figure 2 . For sample P11#, an absorption peak appeared at 3620 cm -1 , which was due to the electron transfer of O 2- →Co 2+ . However, no absorption peak appeared at 3620 cm -1 for Comparative Example samples D1# and D2#. This indicates that the catalyst prepared by the "dissolution-recrystallization" method can successfully incorporate metallic cobalt into the zeolite framework in the form of -Co-O-Si-. The introduction of the metal can effectively inhibit agglomeration and sintering at high temperatures, significantly improving the thermal stability and chemical stability of the zeolite.

[0072] The above Co-modified samples were characterized by ultraviolet-visible spectroscopy. Taking Comparative Example samples D1#, D2#, and Example sample P11# as examples. The positions of the metal in the zeolite pores were defined as α-site (located in the straight pores), β-site (located at the intersection of the straight pores and the sinusoidal pores), and γ-site (located in the sinusoidal pores), and the metal on the zeolite surface was defined as out. As Figure 3 shown, it can be seen that the Co species in Comparative Example D2# were mainly CoOX on the zeolite surface, while the Co species in Comparative Example D1# and Example P11# samples were mainly located in the zeolite pores, which was consistent with the XRD characterization results. The Co 2+ at the β-site is a highly efficient active center for the alkane dehydrogenation reaction of cobalt-based catalysts. With the optimization of the post-treatment conditions, the directional localization of Co 2+ in the zeolite pores was achieved, and the proportion of Co 2+ at the β-site reached 74.3%, greatly improving the reaction activity.

[0073] Example 14: Testing of Propane Dehydrogenation Reaction Activity and Stability

[0074] The reaction was carried out in a stainless-steel tube fixed-bed reactor with an inner diameter of 10 mm. The flow rates of all gas streams required for the experiment were adjusted by mass flow controllers and mixed before flowing into the reaction gas. 500 mg of catalyst (20 - 40 mesh) and 1.0 g of quartz sand (40 - 60 mesh) were weighed and evenly mixed, then placed in the stainless-steel tube and pretreated under N2 atmosphere at 600 °C for 2 h. Then, the activity and stability were evaluated under the following conditions: reaction gas mixture C3H8:CO2:N2 = 1:1:3, reaction gas space velocity 6000 mL / g·h, reaction temperature 600 °C. The activity comparison of each catalyst is shown in Table 5, and the stability comparison is shown in Table 6.

[0075] Table 5: Activity Comparison of Catalysts for Propane Dehydrogenation Reaction

[0076]

[0077] Table 6: Stability Comparison of Catalysts for Propane Dehydrogenation Reaction

[0078]

[0079]

[0080] Example 15: Testing of Ethane Dehydrogenation Reaction Activity

[0081] The reaction was carried out in a stainless-steel tube fixed-bed reactor with an inner diameter of 10 mm. The flow rates of all gas streams required for the experiment were adjusted by mass flow controllers and mixed before flowing into the reaction gas. 500 mg of catalyst (20 - 40 mesh) and 1.0 g of quartz sand (40 - 60 mesh) were weighed and evenly mixed, then placed in the stainless-steel tube and pretreated under N2 atmosphere at 600 °C for 2 h. Then, the activity was evaluated under the following conditions: reaction gas mixture C2H6:CO2:N2 = 1:1:3, reaction gas space velocity 6000 mL / g·h, reaction temperature 600 °C. The activity comparison of each catalyst is shown in Table 7.

[0082] Table 7: Activity Comparison of Catalysts for Ethane Dehydrogenation Reaction

[0083]

Claims

1. A Co@SP S-1 catalyst, characterized in that: Co is highly dispersed in the SP S-1 molecular sieve. A part of Co is encapsulated in the framework of the self-pillared SP S-1 molecular sieve in the form of -Co-O-Si-. On the surface and inside the pores of the molecular sieve, the proportion of Co species at the position of the intersecting pores is ≥70%, and the coating amount of Co in the catalyst is 1-12 wt%.

2. The preparation method of a Co@SP S-1 catalyst according to claim 1, characterized in that: It includes the following steps: (1) Dissolve the cobalt salt in deionized water, add the SP S-1 molecular sieve to it, and stir while heating in a water bath. (2) After the water bath, dry the sample, mix it with the organic base solution, and transfer it to a hydrothermal autoclave for crystallization. (3) After crystallization, filter, wash, dry, and calcine the obtained solid to obtain the Co@SP S-1 catalyst.

3. The preparation method of a Co@SP S-1 catalyst according to claim 1, characterized in that: In step (1), the mass ratio of the cobalt salt solution to the SP S-1 molecular sieve is 5-15:

1.

4. The preparation method of a Co@SP S-1 catalyst according to claim 1, characterized in that: In step (2), the organic base solution is selected from a n-butylamine solution or a tetrabutylammonium hydroxide solution.

5. The preparation method of a Co@SP S-1 catalyst according to claim 1, characterized in that: In step (2), the concentration of the organic base solution is 0.05-0.55 mol / L.

6. The preparation method of a Co@SP S-1 catalyst according to claim 1, characterized in that: In step (2), the mass ratio of the organic base solution to the SP S-1 molecular sieve is 2.5-15:

1.

7. The preparation method of a Co@SP S-1 catalyst according to claim 1, wherein: In step (2), the crystallization temperature is 120-180 °C, and the crystallization time is 24-72 hours.

8. The preparation method of a Co@SP S-1 catalyst according to claim 1, characterized in that: In step (1), the preparation method of the SPS-1 molecular sieve includes stirring and mixing the silicon source, template agent, and water evenly, placing them in a hydrothermal autoclave for crystallization, and filtering, washing, drying, and calcining the obtained solid to obtain the self-pillared SP S-1 molecular sieve.

9. Application of the Co@SP S-1 catalyst according to claim 1 in the dehydrogenation reaction of light alkanes.

10. Use of the Co@SP S-1 catalyst as described in claim 9 in the dehydrogenation reaction of light alkanes, characterized in that: The reaction temperature is 500-700 °C, and the reaction space velocity is 3000-12000 mL / g·h.

Citation Information

Patent Citations

  • Supported cobalt-based catalyst for Fischer-Tropsch reaction as well as preparation method and application of supported cobalt-based catalyst

    CN119608232A

Cited By

  • Cross-pore-rich Co-Silicalite-1 catalyst as well as preparation method and application thereof

    CN121490810A